Knowledge of Extension Agents regarding Professionalization of Extension Services: Evidence from South West Nigeria - Oluwasogo David Olorunfemi; Oladimeji Idowu Oladele (Journal of International Agricultural and Extension Education, 2018)
The study examined the knowledge of agriculture extension agents on professionalization in South West Nigeria. This was borne out of the need to improve and ensure a viable, effective and vibrant extension and advisory service delivery in the area. 301 public and 55 private extension agents were selected through a two-staged sampling procedure. A questionnaire was used to obtain data on their socio-economic characteristics, knowledge on professionalization and its components, these being analyzed using descriptive, t-test and tobit regression analyses. The results showed that the agricultural agents in the public and private extension organizations had a basic knowledge on the concept of professionalization and its components of accreditation, registration and certification. However, disparities in the level of knowledge between the public and private extension personnel were observed. The findings indicated that their educational level and background were significant influencing factors of knowledge on professionalization. The study has implications for educating and training agricultural extension agents on professionalization. Seminars and workshops should be held specifically for the public extension agencies, to upgrade their knowledge and capacity on the concept, intricacies and potential benefits of professionalization on service delivery. This will help assist the institutionalization of professionalization in the agricultural extension sector and enhance competent, accountable and effective extension and advisory services delivery
Keywords: knowledge; professionalization; extension agents; certification; Nigeria